Watching Cultural Hybridity in Hinduism Myth on The PRISMA Series Road to Baliphex 2022 - Oktaviana, Sandra Tri; Sujoko, Anang; Wahyudi, Dicky (Universitas Muhammadiyah Ponorogo, 2023)
The Indonesian Philatelic Association (PFI) collaborated with PT. Pos Indonesia launched a special edition of PRISMA stamps to welcome Baliphex 2022, uniquely on PRISMA stamps there are symbols of ‘Wayang Kamasan’ painting (Balinese) and Mahabharata story (Indian) initiated by PFI. Researchers view that the special edition PRISMA series road to Baliphex 2022 is not just proof of payment and an event promotion tool, but as has meaning in each of the symbols that reflected Balinese and Indian culture. This study aims to reveal the representation of Balinese and Indian cultures in the PRISMA series Road to Baliphex 2022. We use Roland Barthes' semiotic method with units of analysis of denotation, connotation, and mythology. The results show that Balinese culture in PRISMA's Road to Baliphex 2022 series is structured through Mahabharata in Wayang Kamasan symbols, Baliphex events, and stamp elements that have denotative and connotative meanings. The mythology that appears in the PRISMA series Road to Baliphex 2022 is the myth of Hinduism, which is the belief of the majority of Balinese people. Hinduism mythology is structured through the symbolization Saput Poleng, Flags of Kober, Merdah and Tualen, Horse Carts, Big Trees, Ornaments, and Temples. The Hinduism mythology in the PRISMA series Road to Baliphex 2022 is not assembled through a single cultural representation, but with cultural hybrids from Mahabharata (Indian) and Wayang Kamasan (Balinese). This research contributes to the thesis statement that postage stamps can be used by the community as communication media to represent a certain ideology through a series of symbols with cultural hybridity.